The classroom teacher's behavior management toolbox - Pierangelo, Roger; Giuliani, George A., 1938- (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
This book focuses on practical and productive techniques that can be used in a variety of behavior crisis situations that may occur in a classroom. Teachers have told us that one of their major concerns has been dealing with severe behavior problems in the classroom.While there are many different types of crisis situations that may occur having the proper "tools" can prevent a situation from becoming even worse. The Classroom Teacher's Behavior Management Toolbox provides a variety of crisis tools for all types of situations. These tools have been gathered over the years and have been very successful in actual classroom situations.
Keywords: Classroom management -- Handbooks, manuals, etc.; Behavior modification -- Handbooks, manuals, etc.; Education -- Classroom Management.; Teaching skills and techniques.; elektronické knihy; electronic books